Experience Sharing of Retroperitoneal Laparoscopic Ureterolithotomy from a Teaching Hospital - Joshi, R (Journal of Nepal Health Research Council, 2014)
Background: Retro-peritoneal ureterolithotomy may be first option in impacted large upper and mid ureteric stones in selected cases.Methods: We performed 16 Retroperitoneal Laparoscopic Ureterolithotomy in a teaching hospital. Out of 16 cases, eleven stones were located in the upper ureter and rest in mid ureter. Main indication was impacted large stone (1.5- 2cm) (1.72 cm, mean size). Failed extracorporeal shock wave lithotripsy and Uretero-renoscopy were other two indications. Failed PCNL for renal pelvic stone were resorted to open procedure not RUL.Results: Total 16 RUL were performed. Hospital stay in range was 3-11 days. The mean operative time was 96 minutes and mean blood loss was 30 ml. There were 4 failures. No major complications were encountered. Prolong urinary leakage was seen in one patient. Follow up Intravenous urogram at 3 months revealed normal ureter in all cases.Conclusions: RUL is a good option in lieu of open surgery for selected patient with large hard impacted ureteral stone which are likely to resist any endo-urological procedure. Our experience represents a safe and effective treatment option as a first option for large impacted stone or as a salvage second option for failed endo-urological procedure or ESWL.Keywords :Double J stent; retroperitoneal ureterolithotomy; Uretero-renoscopy; Â Urinary tract Infection.